Role of C-reactive protein in osteoclastogenesis in rheumatoid arthritis - Kim, Kyoung-Woon (Arthritis Res Ther, 2015)
INTRODUCTION: C-reactive protein (CRP) is one of the biomarkers for the diagnosis and assessment of disease activity in rheumatoid arthritis (RA). CRP is not only the by-product of inflammatory response, but also plays proinflammatory and prothrombotic roles. The aim of this study was to determine the role of CRP on bone destruction in RA. METHODS: CRP levels in RA synovial fluid (SF) and serum were measured using the immunoturbidimetric method. The expression of CRP in RA synovium was assessed using immunohistochemical staining. CD14+ monocytes from peripheral blood were cultured with CRP, and receptor activator of nuclear factor-κB ligand (RANKL) expression and osteoclast differentiation were evaluated using real-time PCR, counting tartrate resistant acid phosphatase (TRAP)-positive multinucleated cells and assessing bone resorbing function. CRP-induced osteoclast differentiation was also examined after inhibition of Fcγ receptors. RESULTS: There was a significant correlation between CRP levels in serum and SF in RA patients. The SF CRP level was correlated with interleukin (IL)-6 levels, but not with RANKL levels. Immunohistochemical staining revealed that compared with the osteoarthritis synovium, CRP was more abundantly expressed in the lining and sublining areas of the RA synovium. CRP stimulated RANKL production in monocytes and it induced osteoclast differentiation from monocytes and bone resorption in the absence of RANKL. CONCLUSIONS: CRP could play an important role in the bony destructive process in RA through the induction of RANKL expression and direct differentiation of osteoclast precursors into mature osteoclasts. In the treatment of RA, lowering CRP levels is a significant parameter not only for improving disease activity but also for preventing bone destruction.